Short-term evaluation of Cure Violence St. Louis: Challenges, triumphs, and lessons learned - Lentz, Theodore S. (Criminology & public policy, 2024)
Research Summary Firearm violence continues to be a leading cause of death in the United States. As alternatives to law enforcement intervention, community-based violence prevention programs, such as Cure Violence, have become increasingly popular across U.S. cities. This article documents the results of a multiyear, mixed-methods, quasi-experimental study of the implementation and impact of Cure Violence in St. Louis, Missouri, from 2020 to 2023. We analyzed data from semistructured interviews, a two-wave community survey, and police records of neighborhood violence, finding limited evidence of program effectiveness. Although some interview participants stated that the program had a positive impact, we observed no change in community norms/perceptions of violence, and our analysis of police data suggests that program implementation was associated with declining violence in only one of the three intervention sites. Policy Implications This article highlights challenges of implementing and evaluating community-based violence prevention. More work is needed to unpack the mechanisms responsible for turning program activities into measurable impacts in both the short and long term. Implications for planning and evaluating community-based violence prevention programs are discussed.